Xenon protects against blast-induced traumatic brain injury in an in vitro model - Campos,Pires R; Koziakova,M; Yonis,A; Pau,A; Macdonald,W; Harris,K; Edge,C; Franks,N; Mahoney,P; Dickinson,R (Journal of Neurotrauma, 2018)
The aim of this study was to evaluate the neuroprotective efficacy of the inert gas xenon as a treatment for patients with blast-induced traumatic brain injury in an in vitro laboratory model. We developed a novel blast traumatic brain injury model using C57BL/6N mouse organotypic hippocampal brain-slice cultures exposed to a single shockwave, with the resulting injury quantified using propidium iodide fluorescence. A shock tube blast generator was used to simulate open field explosive blast shockwaves, modeled by the Friedlander waveform. Exposure to blast shockwave resulted in significant (p < 0.01) injury that increased with peak-overpressure and impulse of the shockwave, and which exhibited a secondary injury development up to 72 h after trauma. Blast-induced propidium iodide fluorescence overlapped with cleaved caspase-3 immunofluorescence, indicating that shock-wave–induced cell death involves apoptosis. Xenon (50% atm) applied 1 h after blast exposure reduced injury 24 h (p < 0.01), 48 h (p < 0.05), and 72 h (p < 0.001) later, compared with untreated control injury. Xenon-treated injured slices were not significantly different from uninjured sham slices at 24 h and 72 h. We demonstrate for the first time that xenon treatment after blast traumatic brain injury reduces initial injury and prevents subsequent injury development in vitro. Our findings support the idea that xenon may be a potential first-line treatment for those with blast-induced traumatic brain injury.